CARDIOVASCULAR EVENTS IN SYSTEMIC LUPUS ERYTHEMATOSUS: MECHANISMS FOR THE ACCELERATED DEVELOPMENT OF ATHEROSCLEROSIS, DIAGNOSIS, CORRECTION CAPABILITIES - A. V. Arshinov; N. Yu. Levshin; I. G. Maslova (Научно-практическая ревматология)
Atherosclerosis and its complications are the major cause of late mortality among patients with systemic lupus erythematosus (SLE). SLE and coronary heart disease share common pathophysiological mechanisms associated with systemic and chronic inflammation. At the same time, traditional risk factors, such as hypertension, elderly age, smoking, hypercholesterolemia, obesity, and male sex, cannot fully explain the mechanism for the accelerated development of atherosclerosis in patients with SLE. Specific risk factors, such as its duration, glucocorticoid use, anti-doublestranded (native) DNA autoantibodies and antiphospholipid antibodies, create conditions for the accelerated development of atherosclerosis in this group of patients.The available facts indicate that a rheumatologist can reduce the risk of cardiovascular disease (CVD), by controlling the activity of SLE. Traditional CVD risk factors should be also modified with smoking cessation, weight loss, and blood pressure control. It is necessary to keep in mind the role of anti-inflammatory therapy, in particular the positive effect of drugs, such as anti-malarial drugs and mycophenolate mofetil, and the adverse prognostic effect of prolonged glucocorticoid use. Further studies should assist in elaborating effective risk scales and specific therapeutic programs for the prevention and treatment of CVD in patients with SLE.